A re-look into intra-operative impediments and post-operative morbidities in repeat caesarean section - Subramanian, Supraja; Chugh, Amey; Bal, Himadri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Repeat caesarean sections are known to be a cause of significant morbidity in both intra and post-operative period. The challenges faced by the surgeon may include adhesions, difficulty in delivery of foetus, visceral injury and bleeding. The post-operative recovery may be marred by problems such as post-partum haemorrhage, febrile morbidity, wound infections and the after effects of intra-operative visceral injury. It is these issues that often make repeat caesarean section a cause for concern and delay the recovery of the mother. Methods: At random, hundred ante-natal patients visiting the obstetric OPD, meeting the inclusion criteria of previous caesarean section and planned for repeat caesarean section were selected and all the data were collected and tabulated. Results: After careful analysis of the data, it is observed that the intra-operative findings of adhesions, placenta praevia and excessive blood loss were encountered in relook caesarean sections. Similarly post operative morbidity in the form of wound infection and fever were observed in the same study population. Conclusions: If we are more vigilant and restrict the number of primary caesarean sections to evidence based appropriate indications, we may be successful in reducing the number of repeat caesarean sections and thereby mitigating the subsequent hardships for the mother.